A Companion to Saxo Grammaticus - Heebøll-Holm, Thomas K.; Mortensen, Lars Boje (Early Modern History and Modern History E-Books Online, Collection 2024., 2024)
Ever since the publication of Saxo Grammaticus' Gesta Danorum at the beginning of the thirteenth century, scholars and laymen have grappled with the complex and marvellous chronicle. As much specialized scholarship has been published in Danish, this companion breaks new ground by giving a comprehensive and up-to-date tour of the work for a global audience. Attention is given to the unity of Saxo's massive chronicle, whether he is dealing with a legendary pagan past or events from his own time. Saxo's world and views are explored in ways that shed new light on all of northern Europe. Contributors are Bjørn Bandlien, Karsten Friis-Jensen, Michael H. Gelting, Thomas K. Heebøll-Holm, Lars Hermanson, Lars Kjær, Torben Kjersgaard Nielsen, Annette Lassen, Anders Leegaard Knudsen, Lars Boje Mortensen, Mia Münster-Swendsen, Erik Niblaeus, Roland Scheel, Karen Skovgaard-Petersen, Kurt Villads Jensen, and Helle Vogt.